Laboratory-scale investigation of the Ventilated-Trousers device acting as a suppressor of vortex-induced vibrations. (15th September 2017) - Cicolin, M.M.; Assi, G.R.S.
Abstract: Experiments have been carried out with circular cylinders fitted with a suppressor of vortex-induced vibrations called the Ventilated Trousers (VT). Tests were performed at laboratory scale in a free-surface water channel with fixed and free-to-respond models in one degree of freedom. The oscillating tests were performed with elastically mounted cylinders with low mass and damping ( m * ζ < 0.009 ). Reynolds number varied from 5000 to 25000 and reduced velocity varied between 2 and 15. Tests with fixed models showed that the VT increased the mean drag and practically eliminated the fluctuating lift force when compared to a bare fixed cylinder. Free-response tests showed that the VT was able to reduce 60% of the peak amplitude of vibration, thus reducing the maximum drag compared with that of a bare oscillating cylinder. Three hypotheses are proposed to explain the physical mechanism underlying the suppression by the VT: local disruption of vortex shedding; three-dimensional disruption of the near wake; and the increase of hydrodynamic damping. Abstract : Highlights: VIV of a cylinder with VT was characterized through the synchronization range. VT suppressor reduced the VIV peak amplitude of displacement in 60%. VT suppressor increased drag in 25%. We propose three hypotheses to explain the physical mechanism.